The Effect of Cocopeat Addition in Plant Media on The Quality and Quantity of Papaya Seeds (Carica papaya L.var.calina) - Arrijani Arrijani; Iriani Setyawati (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2023)
Papaya (Carica papaya L.) is one of the agricultural commodities that is widely cultivated by farmers in almost all parts of Indonesia. This plant is widely cultivated because varied consumption of papaya by the community makes the demand for fresh papaya fruit in the market always increase. Therefore, the cultivation of this plant is very important to be applied properly. Cocopeat is a powder which is a waste of coconut coir processing. Our previous research has shown that cocopeat is an organic material that has a positive role in the growth of patchouli seedlings. This study aimed to examine how the effect of the addition of cocopeat on the quality and quantity of growth of papaya seedlings (Carica papaya L.var.calina) on experimental land within the Universitas Negeri Manado (Unima) campus in Tondano. Experimental research was carried out with one factor, the concentration of cocopeat, with 5 levels 10, 20, 30, 40 and 50%. The control used was an organic media compounded by the analysis without using cocopeat. Each treatment and control was repeated 30 times so that the number of experimental units was 180 experimental units. Randomization was carried out by placing 10 rows and 18 columns at the Unima Patchouli Nursery Installation. The quantity parameter is the number of days the seeds germinated and the number of seeds that were successfully germinated in each treatment and control. Quality parameters include seedling height at the age of 2 months after germination (first germination); number of leaves, leaf size, wet weight and dry weight at 2 months of age. Based on the results, it can be concluded that the use of organic media with the addition of cocopeat at a concentration of 10-50% had a significant effect on leaf number, leaf size, plant height, stem diameter, wet weight, and dry weight of papaya plants in the early growth period. The addition of cocopeat concentration in the growing media will have an increasing effect on the observed parameters. Especially for the parameter of the number of days of germination after planting did not show a significant difference between all treatments.